2019
DOI: 10.1108/pr-06-2017-0172
|View full text |Cite
|
Sign up to set email alerts
|

The role of group-level perceived organizational support and collective affective commitment in the relationship between leaders’ directive and supportive behaviors and group-level helping behaviors

Abstract: Purpose The purpose of this paper is to examine a model linking directive and supportive leadership to group-level helping behaviors via group-level perceived organizational support (GPOS) and collective affective commitment (CAC). Design/methodology/approach Using data from 115 business units of an international retailer, the authors tested and compared the theoretical model against more parsimonious solutions using χ² difference tests. The hypotheses were examined within a structural model. Findings The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 104 publications
(174 reference statements)
4
35
0
11
Order By: Relevance
“…The finding of this investigation endorses that there is a positive relationship between organizational support and employee engagement, which supports hypothesis H2b. Tremblay, Gaudet [ 79 ] examined 115 business units of an international retailer, and the findings of their research showed that organizational support is positively linked to employee engagement. These findings are also supported by organizational support theory [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finding of this investigation endorses that there is a positive relationship between organizational support and employee engagement, which supports hypothesis H2b. Tremblay, Gaudet [ 79 ] examined 115 business units of an international retailer, and the findings of their research showed that organizational support is positively linked to employee engagement. These findings are also supported by organizational support theory [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding TAC, previous research has aggregated team identification to examine its effect on team performance (Kearney & Gebert, 2009). For example, Tremblay et al (2019) aggregated affective commitment (e.g., “I feel like part of the family at my organization”) to the group level in order to examine group-level perceived organizational support as a mediator between leadership and affective commitment. The aggregation is based on a rationale that TAC represents teachers’ psychological bond to their school.…”
Section: Methodsmentioning
confidence: 99%
“…Committed employees will show more productive behavior and will surpass the supervisor's expectations (Yousef, 2000). Literature suggests that some researchers have found a more significant relationship between procedural justice and OC (Astuti & Ingsih, 2019;Mete & Sökmen, 2019;Tremblay, Gaudet, & Vandenberghe, 2019). While others have claimed that distributive justice has a more significant relationship with OC (Imamoglu, Ince, Turkcan, & Atakay, 2019;Jang, Lee, & Kwon, 2019).…”
Section: Organizational Commitment As Mediatormentioning
confidence: 99%